This preview shows pages 1–5. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: ( Z = 1) + 2 · P ( Z = 2) + 4 · P ( Z = 4) + 8 · P ( Z = 8) + 16 · P ( z = 16) = 14 3 = E ( X ) · E ( Y ) E ( XY ) = E ( Z ) On the next page, we mimic the proof of Lemma 5.28, using these X,Y . Reading the proof with this example in mind, might make the proof more understandable. E ( X ) E ( Y ) = X x ∈{ 1 , 2 , 4 } xP ( X = x ) X y ∈{ 1 , 2 , 4 } yP ( Y = y ) = X x ∈{ 1 , 2 , 4 } X y ∈{ 1 , 2 , 4 } xyP ( X = x ) P ( Y = y ) = X z ∈{ 1 , 2 , 4 , 8 , 16 } z X x,y ∈{ 1 , 2 , 4 } xy = z P ( X = x ) P ( Y = y ) = X z ∈{ 1 , 2 , 4 , 8 , 16 } z X x,y ∈{ 1 , 2 , 4 } xy = z P ` ( X = x ) ∧ ( Y = y ) ´ = X z ∈{ 1 , 2 , 4 , 8 , 16 } zP ( Z = z ) = E ( Z ) = E ( XY ) Ind of X,Y...
View
Full
Document
This note was uploaded on 08/25/2010 for the course COMP COMP170 taught by Professor M.j.golin during the Spring '10 term at HKUST.
 Spring '10
 M.J.Golin
 Computer Science

Click to edit the document details